Corrigendum: A randomized clinical trial of freeze-dried amniotic membrane transplantation and conjunctival-limbal graft for pterygium excision and evaluation of conjunctival inflammation marker in tears (Faculty of Medicine Universitas Indonesia, 2021)
[This corrects the article DOI: 10.13181/mji.oa.203818]